Acute restraint stress activates functional NK1 receptor in the colon of female rats: involvement of steroids - Bradesi, S (Copyright 2002 by Gut, 2002)
Background and aims: Psychological factors have been implicated in the aetiology of irritable bowel syndrome characterised by intestinal altered motility and visceral hypersensitivity. Similar disorders have been found in rats under stressful conditions. The role of tachykinins in bowel dysfunctions caused by stress is not fully documented. Therefore, we investigated the influence of stress on NK1 receptor activation at the colonic level in female rats. Methods: The stress procedure used consisted of two hours of partial restraint. Histamine release was measured from colonic samples of control and stressed animals and the effect of SR140333, a NK1 receptor antagonist, on substance P induced histamine release was determined. Involvement of steroids has been evaluated in this response. Results: NK1 receptor antagonist was found to inhibit substance P induced histamine release in samples from stressed female rats but not in samples from control animals. Previous treatment of female rats with RU 486 abolished this effect observed in stressed animals. Similarly, in samples from stressed female rats previously ovariectomised, SR140333 failed to inhibit substance P induced histamine release but previous treatment with both progesterone and oestrogen restored its effect. Conclusions: Stress induces NK1 receptor activation in the colon, and ovarian steroids are involved in this response.